The relationship between physical activity and academic engagement among college students-the mediating chain effect of trait mindfulness and self-efficacy - Zhengfa Han; Hanyu Ju (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
As a vital indication of academic success and adaptive behavior, academic engagement among college students has garnered significant interest in education. Yet, the relationship between physical activity and academic engagement has received little study, particularly among college students. This study investigates the relationship between academic engagement, self-efficacy, trait mindfulness, and physical activity among college students. This study studied 469 college students using SPSS and AMOS software, CFA, correlation, Bootstrap, and other statistical methods. Physical Activity Rating Measure, Mindful Awareness Attention Scale, General Self-Efficacy Scale, and College student academic engagement scale served as the basis for this study. According to studies, college students' physical activity can have both direct and indirect effects on their academic engagement via the chain mediation of trait mindfulness and self-efficacy. It is recommended that college students engage in physical activity while attending classes to develop long-lasting and consistent fitness routines. In addition to establishing a theoretical and empirical foundation for boosting the academic engagement of college students through physical exercise, this study is expected to increase our understanding of the internal mechanisms behind the effect of physical activity on academic engagement.